2019
DOI: 10.3390/rs11121502
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Temporal Stability Evaluation of Pseudo-Invariant Calibration Sites (PICS)

Abstract: Pseudo-Invariant Calibration Sites (PICS) are one of the most popular methods for in-flight vicarious radiometric calibration of Earth remote sensing satellites. The fundamental question of PICS temporal stability has not been adequately addressed. However, the main purpose of this work is to evaluate the temporal stability of a few PICS using a new approach. The analysis was performed over six PICS (Libya 1, Libya 4, Niger 1, Niger 2, Egypt 1 and Sudan 1). The concept of a “Virtual Constellation” was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Pseudo invariant calibration sites have been proven as the least expensive method of on-orbit calibration. Over the last 14 years, a significant expansion in PICS use has been observed to monitor the long-term top-of-atmosphere (TOA) reflectance trends from different sensors [9][10][11]. These PICS sites are known for their spatial uniformity by manifesting stable spectral characteristics over time, higher reflectance, and negligible atmospheric impact on upward radiance [12].…”
Section: Pics Stability and Identification Of Stable Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudo invariant calibration sites have been proven as the least expensive method of on-orbit calibration. Over the last 14 years, a significant expansion in PICS use has been observed to monitor the long-term top-of-atmosphere (TOA) reflectance trends from different sensors [9][10][11]. These PICS sites are known for their spatial uniformity by manifesting stable spectral characteristics over time, higher reflectance, and negligible atmospheric impact on upward radiance [12].…”
Section: Pics Stability and Identification Of Stable Areasmentioning
confidence: 99%
“…Optimal regions within Libya 4, Niger 1, Sudan 1, Niger 2, Egypt 1, and Libya 1 contemplated less temporal uncertainty. Among them, Libya 4 demonstrated as the most temporally stable site with a temporal variation of less than 3% and could be broadly used in radiometric calibration work [1,3,10,16].…”
Section: Pics Stability and Identification Of Stable Areasmentioning
confidence: 99%
“…For many years, numerous researchers exploited six CEOS-endorsed PICS to monitor the calibration trend of the remote sensing satellite. Among all the PICS, Libya 4 appears to be the most stable site, with from 1% to 1.5% temporal uncertainty [116]. Consequently, Libya 4 is the most frequently used PICS.…”
Section: Pics Based Radiometric Stability Monitoringmentioning
confidence: 99%
“…The use of an AOI with an optimal size reduces the possible uncertainty generated by the dune effect, improving the stability of the indirect calibration [17]. Tuz Zafrin Tuli [18] showed that there is a long-term temporal variability in some PICS.The purpose of this work is to support PICS-based calibration methodologies for medium to high-resolution sensors by locating an Optimized Ground Target location (OGT) within Libya-4 with the highest possible spatial and temporal stability, based on the study of the variability of Libya-4 from a wide temporal series of combined Landsat 8 OLI (L8-OLI) (Operational Land Imager) and Sentinel 2 Multispectral Instrument MSI (S2-MSI) data using a novel numeric methodology. We use the Coefficient of Variation (CV) and a quasi-Newton optimization algorithm [19][20][21] combined with a global optimization technique [22] to constrain a search area small enough to perform a final brute-force refinement in order to define the zone with the size and optimal space-time stability.…”
mentioning
confidence: 99%
“…The use of an AOI with an optimal size reduces the possible uncertainty generated by the dune effect, improving the stability of the indirect calibration [17]. Tuz Zafrin Tuli [18] showed that there is a long-term temporal variability in some PICS.…”
mentioning
confidence: 99%